2021
DOI: 10.1073/pnas.2103304118
|View full text |Cite
|
Sign up to set email alerts
|

Soluble mannose receptor induces proinflammatory macrophage activation and metaflammation

Abstract: Proinflammatory activation of macrophages in metabolic tissues is critically important in the induction of obesity-induced metaflammation. Here, we demonstrate that the soluble mannose receptor (sMR) plays a direct functional role in both macrophage activation and metaflammation. We show that sMR binds CD45 on macrophages and inhibits its phosphatase activity, leading to an Src/Akt/NF-κB–mediated cellular reprogramming toward an inflammatory phenotype both in vitro and in vivo. Remarkably, increased serum sMR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 40 publications
(51 reference statements)
2
26
0
Order By: Relevance
“…In accordance with other inflammatory diseases discussed above, we recently reported that serum sMR levels were increased in high-fat diet (HFD)-fed obese mice and obese humans, and positively correlated with adiposity (77). Given that the sMR induces a pro-inflammatory phenotype in macrophages as described above and proinflammatory macrophages drive insulin resistance in metabolic tissues, these observations suggested the possibility that sMR-mediated proinflammatory macrophage activation in obesity may contribute to metabolic dysfunctions.…”
Section: Smr Is a Novel Driver Of Metaflammationsupporting
confidence: 81%
See 4 more Smart Citations
“…In accordance with other inflammatory diseases discussed above, we recently reported that serum sMR levels were increased in high-fat diet (HFD)-fed obese mice and obese humans, and positively correlated with adiposity (77). Given that the sMR induces a pro-inflammatory phenotype in macrophages as described above and proinflammatory macrophages drive insulin resistance in metabolic tissues, these observations suggested the possibility that sMR-mediated proinflammatory macrophage activation in obesity may contribute to metabolic dysfunctions.…”
Section: Smr Is a Novel Driver Of Metaflammationsupporting
confidence: 81%
“…Importantly, a recent study demonstrated that the sMR can actually drive proinflammatory macrophage activation ( 77 ). sMR induced an inflammatory phenotype of both murine and human macrophages, as reflected by increased secretion of proinflammatory cytokines (TNF, IL–6, IL–12 and IL–1β) and a shift in cellular metabolism towards increased glycolysis ( 77 ), a hallmark of proinflammatory macrophage activation ( 78 ).…”
Section: Smr Correlates With Inflammatory Diseases and Induces Macrophage Activationmentioning
confidence: 99%
See 3 more Smart Citations